Saline dressing versus povidone iodine dressing in chronic diabetic foot ulcer healing: a prospective comparative study - Kulkarni, Srinivas B.; S., Venkatesh; R., Kruthi S. (International Surgery Journal, 2019)
Background: Numerous topical agents are used for chronic diabetic foot ulcer (DFU) care and healing. In most of the hospitals in India povidone iodine is used topically for DFU dressing, however few other agents are more efficacious; the present study was aimed to compare the effect of povidone iodine and normal saline dressing in healing of DFU. Methods: A total of 50 patients (25 patients in each arm of povidone Iodine and Saline dressing group) with complaints of chronic DFU attending surgery outpatient department of Rajarajeswari Medical College and Hospital were considered in this prospective comparative study from July 2017 to December 2018. Dressings were done on daily basis for a period of 6 weeks, and the results were compared on 2nd, 4th and 6th week, using reduction in surface area of chronic DFU as parameter of healing process. Results: The mean surface area of wound in povidone iodine group was: baseline- 12.2 sq.cm, 2nd week- 11.7 sq.cm, 4th week- 10.6 sq.cm, 6th week- 9.8 sq.cm; While in saline group was: baseline- 13.3 sq.cm, 2nd week- 11.6 sq.cm, 4th week- 10.8 sq.cm, 6th week- 9.6 sq.cm. After 6 weeks, the mean reduction in surface area of wound is more in the saline dressing group compared with the povidone iodine dressing group and the results are statistically significant at a p<0.05. Conclusions: Saline dressing is more effective than povidone iodine dressing in achieving complete healing, reducing wound surface area, and increasing comfort in subjects with chronic DFU.